Estimasi Pengaruh Vaksin DPT pada Kematian Anak: Analisis Diskritif Data Surveilan Demografi dan Kesehatan di Kabupaten Purworejo - Siswanto Agus Wilopo (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: Recent controversial reports suggest that recipients of one dose of DTP vaccine have higher mortality than children who have received no DTP vaccine. Those reports were mainly derived from African countries where mortality and malnutrion were higher than Indonesia.Objectives: To describe specific and non-specific effects of DTP vaccination on child mortality age 1-24 months under routine vaccination program in Indonesia.Methods: During period of January 1 1995 to August 31, 2001 our longitudinal surveillance data at Purworejo district provided information on 5647 children below 24 months of age who received DTP and other vaccinations. The main outcome measure was all-cause mortality. Vaccination status on DTP, BCG, and measles were collected every 90 days and recorded its time at vaccination. Confounding factors associated with mortality were also collected. This first report used descriptive analysis and a survival curve (Kaplan-Meier) to examine the differential of mortality according to sex of the children and among vaccinated and non-vaccinated children with DTP, BCG, and measles vaccines. The second report will use survival analysis to estimate specific and non-sprecific effects of DTP by considering time at vaccination and other counfounding factors.Results: There is no sex differential of mortality among children in Purworejo. A probability of dying was lower in the children vaccinated with DTP vaccine compared with those not vaccinated DTP. Simmilarly, vaccinated children with BCG and measles have lower mortality compared to unvaccinated children. There is strong indication that BCG and measles have stronger protected effects to risk of dying than DTP.Conclusion: The study showed lower mortality among children who received DTP, BCG, and measles vaccines compared those unvaccinated. There were not enough evidences to change current vaccination policy because DTP was not associated with any harmful effect among girls.Keywords: non-specific effects, DTP vaccine–child survival- Kaplan Meier’s Curve